Holistic framework for land settlement development project sustainability assessment: Comparison of El Hierro Island hydro wind project and Sivens dam project. (8th May 2017) - Roth, A.; Gerbaud, V.; Boix, M.; Montastruc, L.
Highlights: A framework to describe and assess the sustainability of land settlement projects. We set the framework as a metamodel in the model driven engineering perspective. We describe it with architectural, structural, functional, behavioural views. We compare two case studies: El Hierro hydro-wind project and Sivens dam project. Participatory process is a key factor of a development process. Abstract: Project developer in the domain of land settlement project are involved with many stakeholders and are usually overflown by data relative to technical, economic and social issues. This paper contributes to the necessary multi-scale approach challenge and we propose a holistic framework that enables to describe the development process of land settlement project and assess its sustainability. It would help developers to take decisions compliant with the project complexity. In the model driven engineering perspective, the metamodel framework is described with the ISO 19440 four views to represent complex systems: architectural, structural, functional and behavioural. We confront it to describe two case studies: the successful project of hydro-wind power plant in El Hierro in the Canaries, and the Sivens Dam project in France sadly famous for its deadly outcome. Their comparison enables us to draw hypothesis on what are the ingredients of success and validate the framework.